Perkembangan Tafsir dan Mufasir Turki pada Masa Kesultanan Turki Utsmani - Kholil Muttaqin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study examines the intellectual and institutional development of the Qur'anic exegetical tradition (tafsir) in the Ottoman Empire (1299–1922), highlighting tafsir as a core discipline within the madrasa curriculum since the establishment of the Iznik Madrasa (1331). While preserving the authority of classical works such as al-Bayḍāwī’s tafsir, the tradition also developed methodologically through ḥāšiya (glosses) and šarḥ (commentaries) as instruments of scholarly verification (taḥqīq) within the framework of Sunni-Maturidi theology and the Hanafi legal school. Exegetical authority was reinforced through the Huzur Dersleri, an academic forum held before the Sultan that functioned as both scholarly engagement and theological legitimation of state policies. In the nineteenth century, responses to Western modernity encouraged more contextual approaches to tafsir, reflected in the rise of print culture, the use of the Turkish language, and its integration into modern higher education institutions such as Dârülfünûn. This research employs a qualitative descriptive-analytical approach based on intellectual history and bibliographical studies, utilizing ISAM and DergiPark databases alongside biographical and academic sources. The analysis is conducted diachronically and taxonomically to trace paradigm shifts and map the contributions of more than thirty key figures. The study concludes that the Ottoman tafsir tradition served as a bridge between classical Islamic scholarship and the formation of modern Islamic identity in Turkey.